Acquired factor V inhibitors in a polytraumatized patient - Tukić Ljiljana; Stamatović Dragana; Tarabar Olivera; Elez Marija; Zorić Miodrag; Mandić-Radić Slavka (Vojnosanitetski Pregled)
Background. Factor V (FV) inhibitors are a rare disorder reported for the first time about fifty years ago, mostly with the unknown cause. The appearance of FV inhibitors is usually preceded by surgery, infections, administration of antibiotics or transfusions. Clinical manifestations of the presence of FV inhibitors vary from mild to severe and in some instances fatal hemorrhage. Case report. A healthy 51-year-old man with severe multiple injuries (traffic accident), and hemorrhage, which occurred during the orthopedic treatment, was admitted with hemoptysis, epistaxis and hematoma of the right upper leg, and with prolonged prothrombin time (PT), and activated partial thromboplastin time (aPTT). Treatment with vitamin K, fresh-frozen plasma and cryoprecipitate stopped the hemorrhage, but the results of coagulation tests were not normalized. The correction of aPTT and PT with normal plasma showed the decreased activity of FV (1%) due to the presence of inhibitors (titer 17.5 IU). The abnormal results of coagulation tests remained for three weeks, but without clinically manifested hemorrhagic syndrome. At the fourth week after the appearance of FV inhibitors PT, aPTT and the activity of FV became normal and antibodies disappeared spontaneously. Conclusion. Our patient with polytrauma developed a mild hemorrhagic syndrome due to the presence of FV inhibitors five weeks after the accident. Hemorrhage was treated with substitution therapy. The cause of the development of FV inhibitors was unclear (“fibrin glue” was not used during the orthopedic treatment). Factor V inhibitors disappeared spontaneously within four weeks. The fast spontaneous disappearance of FV inhibitors in our patient, confirmed the observations of some authors that they disappeared faster in those patients who were surgically treated prior to their appearance.